Управління конкурентоспроможністю ВНЗ в сучасних соціально-економічних умовах - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А.; Криштоф, С. Д.; Воронюк, О. І. (Ways to Improve Construction Efficiency, 2013)
Disclosed the concept of competitiveness of the university, external and internal factors that determine the marketing survey conducted educational services.